2014
DOI: 10.5888/pcd11.140126
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation and Sex Differences in Adult Chronic Conditions, Health Risk Factors, and Protective Health Practices, Oregon, 2005–2008

Abstract: IntroductionResearch on lesbian, gay, and bisexual (LGB) individuals’ health and health practices has primarily consisted of convenience studies focused on HIV/AIDS, substance use, or mental illness. We examined health-related disparities among Oregon LGB men and women compared with heterosexual men and women using data from a population-based survey.MethodsData from the 2005 through 2008 Oregon Behavioral Risk Factor Surveillance System were used to examine associations between sexual orientation and chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 24 publications
3
46
3
Order By: Relevance
“…6,13,15,18 In contrast to these population-based studies, bisexual women in our study were on average, reporting consuming more fruits and vegetables than heterosexual women, although there were no differences between lesbian and heterosexual women. While fruit and vegetable consumption is an important aspect of dietary intake, it represents only a small part overall.…”
Section: Discussioncontrasting
confidence: 97%
“…6,13,15,18 In contrast to these population-based studies, bisexual women in our study were on average, reporting consuming more fruits and vegetables than heterosexual women, although there were no differences between lesbian and heterosexual women. While fruit and vegetable consumption is an important aspect of dietary intake, it represents only a small part overall.…”
Section: Discussioncontrasting
confidence: 97%
“…Sexual minorities do not represent a single homogenous group and there is evidence that risk varies across sexual orientation categories. 31,32 In the current study, bisexually identified individuals characterized 62% of the sexual minority group and therefore findings may be more reflective of experiences of bisexual cancer survivors than other sexual minorities. Future work with larger samples of sexual minority cancer survivors may reveal statistically significant differences in health behaviors that we were unable to detect in our study.…”
Section: Health Behaviors and Health Among Cancer Survivorsmentioning
confidence: 73%
“…This supports findings of O’Driscoll et al who identified bisexual-identified individuals as having a greater risk for an overdose event [16], however, extensive reports on mortality risk in sexual minority PWID are lacking. Gay/lesbian-identified individuals are at higher risk for suicide attempts, smoking, and binge drinking episodes [41, 42]. Further, sexual minorities are at higher risk of early mortality in communities with a high level of social marginalization [32, 33], which could be important when considering the social marginalization already faced by PWID.…”
Section: Discussionmentioning
confidence: 99%